Corporate document mining for technology intelligence: an analysis of needs, utilisation and possibilities. (20th October 2011) - Lee, Sungjoo; Mortara, Letizia; Kerr, Clive; Phaal, Robert; Probert, David
This paper focuses on document data, one of the most significant sources for technology intelligence. To help organisations use their knowledge in documents effectively, this research aims to identify what organisations really want from documents and what might be possible to obtain from them. The research involves a literature review, a series of in-depth/on-site interviews and a descriptive analysis of document mining applications. The output of the research includes: a document mining framework; an analysis of the current condition of document mining in technology-based organisations together with their future requirements; and guidelines for introducing document mining into an organisation along with a discussion on the practical issues that are faced by users.